Effects of different levels of acidity of lemon juice on E. coli present on fresh spinach - VenJohn, Shelby; Weitlich, M.; Smothers, J.; Smalley, H.; Shearon, C.; Sprouse, J.; Stange, E.; Sparks, H.; Jones, Cassandra K.; Trinetta, Valentina (My University, 2017)
Introduction: E. coli is a common microorganism found on various types of common foods such as produce, meat and even flour. If ingested into the body E. coli can cause serious abdominal issues. This study was done to see how acidity of lemon juice affects the growth of E. coli. Purpose: The objective of this study was to investigate whether the acidity of lemon juice at two different levels destroyed E. coli on spinach. a Methods: 100 grams of spinach was inoculated with E.coli and 100 grams was left as a negative control. For three days bags of spinach were stomached and plated on PCA, PDA and McConkey plates. The inoculated spinach was treated with lemon juice, one bag with a pH of 2 and one bag with a pH of 4. The pH of 4 lemon juice was diluted with water to reach that level. The negative control spinach was only stomached and plated on the first two days. Results: In this experiment it was found that the lemon juice with a pH level of 2 did kill the E. coli but the pH 4 lemon juice did not. On the PCA plates there was P value of .002. This is significantly lower than .05 which showed that the numbers were significantly changed with this treatment. pH of 4 barely changed the plate count on all three medias. The P values of different days were also significant. Day three had a lower count on the McConkey plates. Significance: This study was significant because it proved that a low acidity does kill E. coli. This may be important because often salad dressings can have a low acidity or if lemon juice was to be added to a dressing it could kill E. coli.
Keywords: Fall 2017